Analisis Kontribusi, Efektivitas dan Pertumbuhan Penerimaan Pajak Daerah dan Retribusi Daerah Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Tana Toraja - Juliana Sartika Djafar (ECONBANK: Journal of Economics and Banking, 2022)
This study aims to determine and analyze the contribution of regional tax revenue, regional retribution to Regional Original Income and analyze the effectiveness and growth rate of regional taxes and regional levies in Tana Toraja Regency in 2016-2020. The method used in this study is a descriptive method with a quantitative approach. The results of this study indicate: (1) The contribution of local taxes to the PAD of Tana Toraja Regency is categorized as very low where the average percentage reaches 9.31%. (2) The contribution of regional retribution to PAD is categorized as very low with an average percentage of 8.17%. (3) The level of effectiveness of the local tax of Tana Toraja Regency is classified as effective with an average of 90.36% and the growth rate has fluctuating growth with the highest percentage in 2019 of 33.13% and the lowest percentage in 2020 of -10.88%. (4) The level of effectiveness of regional levies in Tana Toraja Regency is classified as less effective with an average of 73.61%, and the growth rate of regional levies in Tana Toraja Regency has decreased from year to year where the highest percentage occurred in 2017 of 37.78% and The lowest percentage growth rate occurred in 2020 at -45.92%.